1958
DOI: 10.1149/1.2428837
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Oxygen in Zirconium and Its Relation to Oxidation and Corrosion

Abstract: The diffusion of oxygen in zirconium and dilute zirconium alloys has been studied in the temperature range of 400° to 5857deg;C by observing the rates of dissolution of anodically deposited interference oxide films. The diffusion coefficient of oxygen in zirconium depends on the grain orientation and varies by a factor of two among different orientations. Macroscopically observed average values obey the equation D,cm2/sec=9.4exp][ )(−51,780±220/RTwhere the activation energy for the diffusion of oxygen in zirco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(23 citation statements)
references
References 1 publication
1
22
0
Order By: Relevance
“…Mg was additionally tested in a range of environments in this work. A well-defined inductive loop was seen in both this study (not shown) and the literature 38,39,44,[82][83][84] when HP Mg and AZ31B were tested in MgCl 2 solution; also reported in NaCl + Subsequently the AC current density cannot fluctuate with coverage and R t overestimates R P . In order to fully capture this characteristic response of Mg, the inductive loop must be analyzed in the determination of corrosion rate when it appears in the data and R P must be calculated by considering low frequency EIS data even if Z" is positive by extrapolation to the zero frequency…”
Section: Selection Of R P Versus R T and Physical Justification Of Insupporting
confidence: 80%
See 3 more Smart Citations
“…Mg was additionally tested in a range of environments in this work. A well-defined inductive loop was seen in both this study (not shown) and the literature 38,39,44,[82][83][84] when HP Mg and AZ31B were tested in MgCl 2 solution; also reported in NaCl + Subsequently the AC current density cannot fluctuate with coverage and R t overestimates R P . In order to fully capture this characteristic response of Mg, the inductive loop must be analyzed in the determination of corrosion rate when it appears in the data and R P must be calculated by considering low frequency EIS data even if Z" is positive by extrapolation to the zero frequency…”
Section: Selection Of R P Versus R T and Physical Justification Of Insupporting
confidence: 80%
“…This last point merits specific attention, since recent criticisms of EIS for Mg have suggested that EIS determined corrosion rates are significant underestimations of the actual rate determined by mass loss and are very similar to corrosion rates determined from a simple three component (Randle's type) equivalent circuit to determine R t 86 . It is however noted that in that work 86 , there was no concurrent validation via ICP-OES (as herein), and the values of B used were below any ever reported (included the authors own), whilst finally the inductive loop is an irrefutable feature of the data (documented by many 38,39,44,50,[82][83][84][87][88][89] ) and it cannot be summarily ignored. As such, a method for treating EIS data for Mg, based on analyses of R p and more typically reported Tafel slope values, is included in the present paper.…”
Section: Selection Of R P Versus R T and Physical Justification Of Inmentioning
confidence: 90%
See 2 more Smart Citations
“…The dissolution rate of the oxide layer inside Zr-2.5Nb alloy is required to model this phenomenon and quantify its behaviour. Earlier oxide dissolution studies are limited to pure zirconium at low temperatures below 600°C [12,13], and thus provide some guidance for determining the oxide dissolution (and re-oxidation) kinetics in Zr-2.5Nb alloy pressure-tube materials. Increasing the initial oxide layer thickness in the Zr-2.5Nb pressure-tube material is expected to provide a thicker oxide layer that would remain after heating within the high temperature range of 600°C to 900°C.…”
Section: Variation Of Steady-state Emissivity With Temperaturementioning
confidence: 99%